2023
DOI: 10.1021/jacs.2c11908
|View full text |Cite
|
Sign up to set email alerts
|

Strong Antibonding I (p)–Cu (d) States Lead to Intrinsically Low Thermal Conductivity in CuBiI4

Abstract: Chemical bonding present in crystalline solids has a significant impact on how heat moves through a lattice, and with the right chemical tuning, one can achieve extremely low thermal conductivity. The desire for intrinsically low lattice thermal conductivity (κ lat ) has gained widespread attention in thermoelectrics, in refractories, and nowadays in photovoltaics and optoelectronics. Here we have synthesized a high-quality crystalline ingot of cubic metal halide CuBiI 4 and explored its chemical bonding and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 74 publications
2
51
0
Order By: Relevance
“…56−58 These antibonding states in the VBM (near-Fermi level) further weaken the chemical bonding and soften the lattice, which promotes structural distortion and creates intrinsic lattice shearing in TlBiSe 2 . 59 We analyzed the local coordination and chemical bonding environment in TlBiSe 2 using real-space descriptors such as charge density and electron localization function (ELF) calculated using DFT. The total charge density of TlBiSe 2 reveals covalent bonding between Bi and Se atoms, confirmed by the overlapping charge densities of Bi and Se (Figure 3b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56−58 These antibonding states in the VBM (near-Fermi level) further weaken the chemical bonding and soften the lattice, which promotes structural distortion and creates intrinsic lattice shearing in TlBiSe 2 . 59 We analyzed the local coordination and chemical bonding environment in TlBiSe 2 using real-space descriptors such as charge density and electron localization function (ELF) calculated using DFT. The total charge density of TlBiSe 2 reveals covalent bonding between Bi and Se atoms, confirmed by the overlapping charge densities of Bi and Se (Figure 3b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Despite this, the relative uncertainties observed here are consistent with the relative uncertainties in other materials in the literature when measured by the same method, and it is clear that both materials retain the glass-like temperature dependence observed in the parallel measurements with no low-temperature peak. 31…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we focus on a chemical bonding signature: highest-occupied valence bands with a strong anti-bonding character in a semiconductor. Recent studies have suggested that anti-bonding chemical bonds are closely related to ultralow thermal conductivities in a range of materials. The advantage of using the anti-bonding character of the highest-occupied valence band as a descriptor is that it can be efficiently analyzed using the crystal orbital Hamilton populations (COHP) method, , which only requires ground-state density functional theory (DFT) calculations. This method can be applied to any inorganic crystal structure and requires only basic structural and compositional information as input and minimal time and computing resources.…”
Section: Introductionmentioning
confidence: 99%